From prison to pit: trajectories of a dispensable population in Latin America. - Klaufus, Christien; Weegels, Julienne (Mortality, 2022)
The prisoner population in Latin America is highly vulnerable to violence and deadly disease due to overpopulation, understaffing and political neglect. The COVID-19 pandemic has worsened their situation. Drawing from empirical research in three countries – Argentina, Colombia, and Nicaragua – this paper analyses three phases of marginalisation in prisoners' trajectories from prison to pit. Our analysis is structured by the triple marginalisation that stretches out from an experienced situation of 'social death' in prison, a legally imposed 'depersonalisation' of the dead prisoners' body, and the 'bare' death of their plastic-wrapped bodies buried without any ceremony in a politically neglected cemetery. This process points to the everyday necropolitical production of marginal deaths and sheds light on marginalised populations' moral conceptions of dying in pandemic times.